The date of Theoderic’s gold medallion - Grierson, Philip (Hikuin, 1985)
Twenty years ago, in his book on the profile Victory type used for their pseudo-imperial tremisses by several Germanic peoples in the sixth century, Wallace Tomasini referred to a suggestion made by me to the effect that Theoderic the Great struck a limited number of ‘VPW’ tremisses (i.e. tremisses having as reverse type a Victory carrying a palm and wreath, in contrast to ‘VGC’ ones on which the Victory holds a globus cruciger) ‘perhaps concurrently with the Theoderic medallion’, and introduced the Victory with palm and wreath as a deliberately non-Byzantine type in Visigothic Spain after he had established himself there in or about 511. Nieither Tomasini nor I questioned the accepted association of the medallion, the denomination that seemed best capable of providing a firm date for any related coins, with Theoderic’s six-month visit to Rome in 500. This was on the occasion of his tricennalia, the celebration of the thirtieth anniversary of his association as king by his father Theodemir, and was marked by a series of splendid public shows and ceremonies. What would be more likely than for these to have included a special issue of coins for public distribution, and for a few specimens of them to have come down to us?